Hårdare tag i arbetslivet? Åtgärder mot arbetsrelaterat våld i facklig press 1978–2004 (Sociologisk Forskning, 2011)
Preventing violence at work: A study of descriptions of safety measures in Swedish trade union journals 1978–2004The purpose of this study is to examine if perceptions of interventions aimed at violence in the workplace have changed since the 1970s. In the beginning of the study period, structural factors are seen as the dominating explanation for workplace violence. The crime perspective rises in the 1990’s and methods of intervention becomes the control- and justice functions of larger society. The result shows search for accountability to be a salient factor for understanding the development towards an increasing use of penal sanctions.